Formation and Development Perspectives of Eurasian Economic Union on the Basis of Equal Relations and Strategic Development of Political Communications - DZHUMAGALIYEVA, Kulyash V.; AUBAKIROVA, Khadisha A.; DEMEUOVA, Nurgul K. (Journal of Advanced Research in Law and Economics, 2020)
The creation of the Eurasian Economic Union is due to the possibilities to form an integration association in the post-Soviet space. The need to create such an association is determined by the high degree of integration of the culture and social system of most republics. The relevance of the study is the search for prospects for the development of the union in the political context based on the requirements of only the economic nature of integration declared during its creation. The novelty of the study is determined by the fact that the analysis of the possibilities of political development of alliance formation is based on the economic dynamics of the issue. In particular, a forecast of the political development of the EAEU is given according to three scenarios, which are divided depending on the chosen degree of integration with the international economic system. The article determines that political development in connection with a correlation with economic development can be predicted for each member of the EAEU individually. The authors of the article reveal the possible paths of political development for the founding countries. The practical significance of the study is determined by the fact that economic development is an effective limiter for forming of any alliance formation. The authors propose to consider aspects of the formation of the general representation in the future in the EAEU bodies on the basis of the poetic consensus.